2009
DOI: 10.1177/1403494809105286
|View full text |Cite
|
Sign up to set email alerts
|

Danish EQ-5D population norms

Abstract: The calculated mean values for the EQ-5D index score may be used as reference values for comparative purposes in future Danish population health and evaluative studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
188
6
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(219 citation statements)
references
References 16 publications
23
188
6
2
Order By: Relevance
“…Comparison of our results with population studies in other countries showed similar findings, with most problems reported in the pain/discomfort dimension, followed by the anxiety/depression dimension, more problems with increased age and women reporting worse health than men (Burström et al, 2001;Kind et al, 1998;König et al, 2009;Leung et al, 2007;Lubetkin et al, 2005;Sun et al, 2010;Sorensen et al, 2009;Szende & Williams, 2004;).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Comparison of our results with population studies in other countries showed similar findings, with most problems reported in the pain/discomfort dimension, followed by the anxiety/depression dimension, more problems with increased age and women reporting worse health than men (Burström et al, 2001;Kind et al, 1998;König et al, 2009;Leung et al, 2007;Lubetkin et al, 2005;Sun et al, 2010;Sorensen et al, 2009;Szende & Williams, 2004;).…”
Section: Discussionsupporting
confidence: 72%
“…This might be due to several reasons other than the difference in health status between populations. The age and sex structure might be different across countries, or people in different countries might refer to levels of health differently (Szende & Williams, 2004;Sorensen et al, 2009;Bharmal, & Thomas, 2006), or again the mode of administration might vary from one survey to another (Bowling, 2005;Weinberger, Oddone, Samsa, & Landsman, 1996), or some countries include proxy respondents. Therefore, one needs to be cautious when making international comparisons of population health status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EuroQol [29,30] (EQ-5D) is a standardized instrument measuring health status-related quality of life consisting of a health status index (EQ index 0 to 1 scale) and a visual analogue scale (EQ VAS 0 to 100 scale).…”
Section: Methodsmentioning
confidence: 99%
“…Countries included in the analysis were: Argentina, Belgium, China, Denmark, England, Finland, France, Germany, Greece, Hungary, Italy, Korea, the Netherlands, New Zealand, Slovenia, Spain, Sweden, Thailand, United Kingdom, and the United States [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For two countries (Argentina and China), the dataset transfer to the central archive was not possible.…”
Section: Datamentioning
confidence: 99%